Critical Thinking in Pre-Service English Teachers: Evaluating and Promoting Analytical Skills through Academic Writing - Rodriguez-Escobar, Claudia; Carmen Kanelos Saldías (Journal of Teacher Training and Educational Research, 2025)
Critical thinking is acknowledged to be essential for the educators of the 21st century. Consistent with this, this research project aimed to evaluate the critical thinking abilities of third-year students of the English Teacher Training Programme at a Chilean university, who completed their initial two years of academic instruction exclusively online due to the COVID-19 pandemic. During the diagnosis stage, these pre-service teachers were asked to write a short essay about a topic covered in class. This phase showed participants’ lack of comprehension of the topics as their essays tended to address the issues superficially and present weak arguments, and pre-test results confirmed this. Therefore, four pedagogical interventions were designed and implemented throughout the term, using academic writing as a tool to develop critical thinking abilities. These interventions consisted of continuous feedback on the participants’ writings, an academic writing course, attendance at a webinar on critical thinking and English language teaching, and group reflection sessions. The results of the post-test showed significant improvement in both content organisation and the quality of the arguments presented in the essays. The participants demonstrated a more critical and analytical approach to addressing the topics of their writings, demonstrating a significant progress in their analytical reasoning skills. This research highlights the importance of addressing and strengthening critical thinking skills in pre-service teachers, especially after being immersed in a virtual education context. The pedagogical interventions implemented proved to be effective in improving participants’ critical reasoning, representing a valuable contribution to their future teaching practice.